Bio-economic evaluation of a reduced phosphorus supplementation strategy for a cow-calf system in Brazil: a case study - Lopes, Samara P.; Garcia, Felipe Z.; Souza, Vinícius C. [UNESP]; Costa, Diogo Fleury A.; Malafaia, Pedro (Springer Nature, 2018)
Fertility, weight of calves at weaning, and the economic aspects of a breeding herd receiving mineral supplements containing 75 or 12.5 g of phosphorus (P)/kg were measured from 2013 to 2016. No differences in reproduction parameters or weight at weaning were found before and after the adoption of the new scheme of mineral supplementation. Before the study, the annual cost with the formula containing more P was equivalent to 29.3 weaned beef calves; after the P reduction, the annual cost was equivalent to 2.2 to 6.8 weaned calves. After 3 years of supplementation with 12.5 g P/kg no signs of P deficiency were observed. The clinical-nutritional diagnosis of the herd indicated no cause-effect of P content of mineral supplements upon fertility or performance of healthy cows, demonstranting that the adequate forage allowance was enough to meet most P required by the cows.
Keywords: Cost of production; Mineral supplementation; Phosphorus